Long‐term indoor gunshot exposure of special police forces induces bronchitic reactions and elevated blood lead levels—The Berlin shooting range study. Issue 1 (20th December 2022) - Witt, Christian; Kienast, Camilla; Bölke, Georg; Hoffmann, Christina; Roehle, Robert; Bender, Olaf; Nowak, Dennis; Tauber, Rudolf; Gunga, Hanns‐Christian; Hoffmann, Peter; Coats, Andrew J.S.; Liebers, Uta
Abstract: Background: Gunshot emissions contain toxic elements that can harm those frequently exposed, such as police officers. Several years ago, police indoor firing ranges were closed by the Berlin municipality in response to police officer health complaints, and an investigation was launched into the possible respiratory health risks of frequent gunshot emission exposure. We, therefore, conducted an exploratory cross‐sectional study to investigate clinical and functional parameters of respiratory health as well as the burden of trace elements in policemen with long‐term high exposure to indoor gunshot emissions, compared to low‐exposure and control groups. Methods: We conducted lung function tests and collected blood and urine samples from Berlin police officers and government employees who were divided into three subject groups based on exposure to gunshot emissions: high exposure ( n  = 53), low exposure ( n  = 94) and no exposure ( n  = 76). Lung function was examined using body plethysmography. Blood and urine samples were tested via inductively coupled plasma mass spectrometry for the presence of common gunshot powder elements (antimony, lead and manganese). Exposure and symptoms were assessed using records as well as questionnaires. Results: Higher exposure was associated with more respiratory symptoms during gun shooting practice (64% vs. 21%, P  < 0.001) compared to the low‐exposure group. Headache, cough, discoloured mucous and shortness of breath were also more common as were some other symptoms. The cough symptomatology of the high‐exposure group also persisted significantly longer (median: 0.67 vs. 0.01 days, range: 0 to 5 days, P  = 0.029) compared to the low‐exposure group. They also showed a lower forced expiratory volume in 1 s/forced vital capacity quotient (Tiffeneau index), P  = 0.018 between the three groups and P  = 0.005 for the high‐exposure group, a possible marker of early, subclinical bronchial obstruction. We observed increased blood lead concentrations depending on subject's age (+1.2% per year, 95% confidence interval: 0.5–1.9%, P  < 0.001) and cumulative gunshot exposure (+0.34% per 100 000 shots, 0.02–0.66%, P  = 0.037). Conclusions: These first results suggest that long‐term exposure to indoor gunshot emissions induces bronchitic reactions due to repeated irritation of the airways. Higher levels of exposure lead to more negatively impacted lung function and higher blood lead levels with the possible reason that more frequent exposure may mean shorter regeneration phases for the respiratory mucous membrane. We recommend a reduction of exposure to gunshot emissions in order to decrease symptoms and avoid any—even small—deterioration in spirometry.